(untitled) (Eurasian Research Bulletin, 2024)
The article discusses the importance of mastering correct pronunciation while learning a foreign language, especially the phonetic aspect. The article highlights the challenges of mastering the articulation skills of Chinese as compared to English due to the unusual set of vowels and consonants as well as the presence of a melodious variation of sound height when pronouncing syllables (tones). The article also emphasizes the need for teaching phonetics to foreign students due to the increasing international cooperation between China and European countries. The article provides a contrastive analysis of Chinese and English syllables and uses descriptive-analytical, classification, linguistic-cultural, and quantitative analysis as research methods. The article concludes with the main results and general conclusions of the research